The analysis of a dominant gender discourse - Part 2 - Laetitia Zeeman; Marie Poggenpoel; Chris Myburgh (AOSIS, 2002)
Gender dilemmas are formed where a woman's role and identity is constructed in alternative ways, ways which do not cohere with the ways prescribed and expected within a dominant gender discourse. Opsomming Gender-dilemmas wordgevorm waar 'n vrou se rol en identiteit gekonstrueer is op alternatiewe wyses wat nie ooreenstem met tradisionele konstruksies binne 'n dominante gender-diskoers nie. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.